Air‐Permeable Waterproofing Electrocardiogram Patch to Monitor Full‐Day Activities for Multiple Days. Issue 12 (24th March 2022) - Oh, Joosung; Jang, Seok Geun; Moon, Sungmin; Kim, Junho; Park, Hyung Keun; Kim, Hyoung Seop; Park, Sung‐Min; Jeong, Unyong
Abstract: On‐skin healthcare patch‐type devices have great technological challenges in monitoring full‐day activities and wearing for multiple days without detachment. These challenges can be overcome when the sensor is air permeable but waterproof. This study presents a light‐weight, highly stable, and stretchable Au electrode that is fabricated by sputtering on an imidized nanofiber mat. The contact surface of the electrode is hydro‐wetting and the outer surface of the electrode is hydrophobic, so the porous electrode simultaneously has excellent sweat permeability and waterproofing capabilities. The electrode is applied to the electrocardiogram sensor for monitoring the cardiac signals for five consecutive days without detaching while doing various full‐day activities such as relaxing, exercising, showering, and sleeping. This study suggests a modular setup of the electrodes and the cardiac signal processing unit for activating the device when cardiac monitoring is required. Abstract : A patch‐type electrocardiogram (ECG) sensor that is air‐permeable and hydro‐wetting on the sensing part but waterproofing on the outer surface is fabricated. The ECG sensor can provide the cardiac signals during typical daily activities without detaching for five days, such as exercising, showering, and sleeping.